Successfully reported this slideshow.
We use your LinkedIn profile and activity data to personalize ads and to show you more relevant ads. You can change your ad preferences anytime.

comp diff

640 views

Published on

Published in: Business, Technology
  • Be the first to comment

  • Be the first to like this

comp diff

  1. 1. Composite functions
  2. 2. f(x) = x 2 x x 2 2 4 7 49 g(x) = x + 1 2 3
  3. 3. f(g(x)) f(x) = x 2 g(x) (g(x)) 2 x g(x) = x + 1 x x+1 (x+1) 2
  4. 5. f x x f x ( ) ( ) ( ) ? = + Þ ¢ = 1 2 f x x x x ( ) ( ) = + = + + 1 2 1 2 2 Þ ¢ = + f x x ( ) 2 2 f x x f x ( ) ( ) ( ) ? = + Þ ¢ = 3 2 f x x x x ( ) ( ) = + = + + 3 6 9 2 2 Þ ¢ = + f x x ( ) 2 6 = + 2 1 ( ) x = + 2 3 ( ) x
  5. 6. f x x f x x ( ) ( ) ( ) ( ) = + Þ ¢ = + 1 2 1 2 f x x f x ( ) ( ) ( ) = + Þ ¢ = 7 2 f x x f x x ( ) ( ) ( ) ( ) = + Þ ¢ = + 3 2 3 2 2 7 ( ) x + f x x x x f x x x ( ) ( ) ( ) ( ) = + = + + Þ ¢ = + = + 7 14 7 2 14 2 7 2 2
  6. 7. f x x f x ( ) ( ) ( ) = + Þ ¢ = 2 3 2 2 2 3 ( ) x + 2 5 2 ( ) x + f x x x x x x f x x x ( ) ( ) ( )( ) ( ) ( ) = + = + + = + + Þ ¢ = + = + 2 3 2 3 2 3 4 12 9 8 12 4 2 3 2 2 Oops f x x x x f x x x ( ) ( ) ( ) ( ) = + = + + Þ ¢ = + = + 5 2 25 20 4 50 40 10 5 2 2 2 Oops again = + 2 2 2 3 . ( ) x = + 5 2 5 2 . ( ) x f x x f x ( ) ( ) ( ) = + Þ ¢ = 5 2 2
  7. 8. f x x f x ( ) ( ) ( ) = + Þ ¢ = 7 3 2 7 2 7 3 . ( ) x + f x x x x f x x x x ( ) ( ) ( ) ( ) . ( ) = + = + + Þ ¢ = + = + = + 7 3 49 42 9 98 42 14 7 3 7 2 7 3 2 2 f x x f x ( ) ( ) ( ) = + Þ ¢ = 2 1 3 2 3 2 1 2 . ( ) x + f x x x x x f x x x x x x x ( ) ( ) ( ) ( ) ( ) . ( ) = + = + + + Þ ¢ = + + = + + = + = + 2 1 8 12 6 1 24 24 6 6 4 4 1 6 2 1 2 3 2 1 3 3 2 2 2 2 2
  8. 9. f x x ( ) ( ) = + 2 2 1 f x x x x f x x x ( ) ( ) ( ) = + = + + Þ ¢ = + 2 2 4 2 3 1 2 1 4 4 = + = + 4 1 2 2 1 2 2 x x x x ( ) . ( )
  9. 10. f(x)= ( 2x + 3 ) 2 ⇒fʹ(x) = 2 . 2 (2x+3) 1 f(x) = ( 7x + 3 ) 2 ⇒fʹ(x) = 7 . 2 (7x + 3) 1 f(x) = ( 2x + 1 ) 3 ⇒ fʹ(x) = 2 . 3 (x + 1) 2 f(x) = ( x 2 + 1 ) 2 ⇒ fʹ(x) = 2x . 2 (x 2 + 1) 1 f(x) = ( x 3 + 3x 2 - 4x + 1 ) 7 ⇒ fʹ(x) = (3x 2 + 6x -4) . 7 (x 3 + 3x 2 -4x + 1) 6

×